AB0151 Stress moderation impacting lupus with exercise (S.M.I.L.E.): influence of daily moderate exercise and stress modification on autoimmune-mediated inflammation in mice and humans with lupus. (15th June 2017) - Young, NA; Thomas, E; Snoad, B; Sharma, J; Mobeen, M; Yedimenko, J; Steigelman, H; Meara, A; Valiente, G; Ardoin, S; Powell, N; Sheridan, J; et al.
Abstract : Background: Despite numerous studies indicating the positive effects of exercise and psychological stress reduction in patients with autoimmune disease, these therapeutic modalities are currently underemphasized due to the absence of comprehensive immunological characterization and regimen standardization. Objectives: In order to examine the influence on the immune system at the cellular and tissue level, disease pathology was analyzed in the NZM2410 mouse model of lupus nephritis. To translate these results and begin to characterize a consensus treatment regimen, a pilot cohort of systemic lupus erythematosus (SLE) patients with active disease was enrolled into a daily Tai Chi program, which emphasized moderate exercise levels with meditative breathing to provide daily physical activity and stress reduction. Methods: Mice were exercised daily by treadmill walking at moderate intensity. Social disruption stress was induced in mice by disturbing the social order within an established hierarchy. All mice were removed from the study when experimental removal criteria was reached [blood urea nitrogen (BUN)>50 mg/dL; weight loss>20%]. Kidney tissue and serum were collected from mice at experimental endpoint. SLE patients completed daily Tai Chi exercises and data was collected at baseline and throughout the study via questionnaires to access physical activity and stress levels, activity trackers (Fitbit), and serum sample analysis. Results: Histopathological analysis of NZM2410 mice demonstrated that psychosocial stress induction significantly exacerbated and daily moderate exercise significantly reduced lupus nephritis disease pathology, as measured by BUN levels, complement component 3 and IgG complex deposition in glomeruli, pathological grading of H&E-stained kidney sections, and renal macrophage infiltration. Furthermore, stressors induced levels of IL-6, TNF-α, and IL-1β, while exercise suppressed IL-6, TNF-α, IL-10, and CXCL1 in mice. Compared to baseline data, questionnaires confirmed a significant reduction in perceived social stress and an increase in combined metabolic equivalent of task (MET) and overall physical activity in SLE patients. Moreover, fitness activity tracker data showed a significant increase in steps, distance, and activity calories with no changes in body mass index or vigorous activity levels. Interestingly, this correlated with an increased average time in bed each night. Analysis of pro-inflammatory serum cytokine expression revealed suppression in the relative fold change of IL-6 by 23%, IL-8 by 30%, TNF-α by 11%, and IFN-γ by 21% with Tai Chi. Conclusions: These data suggest that moderate exercise and stress management can have potent immunoregulatory effects on the chronic, systemic inflammation associated with SLE and identify daily Tai Chi exercise as a viable adjunct therapy to compliment current pharmacological interventions. References: Wang C, et al. A randomized trial of tai chi for fibromyalgia. The New England journal of medicine 2010, 363(8): 743–754. Acknowledgements: Funding: Center for Integrative Health and Wellness and Wexner Medical Center. Disclosure of Interest: None declared